2016
DOI: 10.21608/jbaar.2016.107547
|View full text |Cite
|
Sign up to set email alerts
|

Biological and histopathological effects of cyromazine on the laevae of Culex pipiens (Diptera Culicidae).

Abstract: Laboratory studies were carried out to investigate the efficacy of the chitin synthesis inhibitor (cyromazine) against all larval stages of Culex pipiens. The compound was tested its efficacy on larval mortality, larval duration, pupation, pupal duration and adult emergence. Also, the histological effects of cyromazine on the midgut, the integument, the fatbodies and the muscles of 4 th larval instar treated as 1 st larval instar were studied. The tested compound increased the larval mortality, decreased the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Also, pronouncedly suppressed enzyme activity was recorded only in the early-aged (1-day old) pupae after treatment with Diofenolan. These results corroborated with those reported results of inhibited ALP activity in certain tissues of some developmental stages of some insects by various IGRs, such as C. pipiens by Diflubenzuron (Yan and Wu, 1990) or Cyromazine (Assar et al, 2012); B. mori by pyriproxyfen (Etebari et al, 2007); in haemolymph of S. littoralis larvae Chlorfluazuron or Flufenoxuron (Anwar and Abd el-Mageed, 2005) and in fat bodies of S. littoralis larvae by Novaluron, Cyromazine or Diofenolan (Hamadah et al, 2016). However, inhibition of ALP activity in larvae and pupae of P. gossypiella, in the present investigation, may be attributed to the effects of tested CSIs, directly or indirectly, on the juvenile hormone and ecdysone regulation (Sridhara and Bhat, 1963).…”
Section: Disturbed Alkaline Phosphatase In P Gossypiella By Novaluron and Diofenolansupporting
confidence: 92%
See 1 more Smart Citation
“…Also, pronouncedly suppressed enzyme activity was recorded only in the early-aged (1-day old) pupae after treatment with Diofenolan. These results corroborated with those reported results of inhibited ALP activity in certain tissues of some developmental stages of some insects by various IGRs, such as C. pipiens by Diflubenzuron (Yan and Wu, 1990) or Cyromazine (Assar et al, 2012); B. mori by pyriproxyfen (Etebari et al, 2007); in haemolymph of S. littoralis larvae Chlorfluazuron or Flufenoxuron (Anwar and Abd el-Mageed, 2005) and in fat bodies of S. littoralis larvae by Novaluron, Cyromazine or Diofenolan (Hamadah et al, 2016). However, inhibition of ALP activity in larvae and pupae of P. gossypiella, in the present investigation, may be attributed to the effects of tested CSIs, directly or indirectly, on the juvenile hormone and ecdysone regulation (Sridhara and Bhat, 1963).…”
Section: Disturbed Alkaline Phosphatase In P Gossypiella By Novaluron and Diofenolansupporting
confidence: 92%
“…According to the currently available literature, increasing activity of acid phosphatase (ACP) was reported in larvae and/or pupae of many insect species after larval treatment with several insect growth regulators (IGRs)(including chitin synthesis inhibitors, CSIs), such as P. gossypiella by pyriproxyfen (Anan et al, 1993); Spodoptera littoralis by Hexaflumuron (Sokar, 1995), Chlorfluazuron, Flufenoxuron and Pyriproxyfen (Abdel-Aal, 2003), Diflubenzuron, Hexaflumuron, Flufenoxuron, Chlorfluazuron, Lufenuron and Tebufenozide (Anwar and Abd el-Mageed, 2005), Chlorfluazuron (Zohry, 2006), Novaluron and Cyromazine (Hamadah et al, 2016); Earias insulana by pyriproxyfen (Anan et al, 1993); Agrotis ipsilon by pyriproxyfen (El-Sheikh, 2002); Culex pipiens by Cyromazine (Assar et al, 2012); Spodoptera litura by Methoxyfenozide (Jian-jun and Tian, 2009); Musca domestica by Buprofezin, Hexaflumuron, Lufenuron, Tebufenozide and Pyriproxyfen (Assar et al, 2010); Ephestia kuehniella by pyriproxyfen (Sharifi et al, 2013); etc. To a great extent, increasing activity of ACP in larvae and pupae of P. gossypiella, as recorded in the present study, are in agreement with those previously reported results, since treatment of full-grown larvae with LC50 values of Novaluron (0.765 ppm) and Diofenolan (0.036 ppm) resulted in elevated activity of ACP in homogenates of larvae (6 hr post-treatment) and pupae (of all ages: 1-, 3-and 7-day old).…”
Section: Disturbed Acid Phosphatase In P Gossypiella By Novaluron and Diofenolanmentioning
confidence: 99%
“…Acetylcholinesterase (AChE) activity: was measured according to the method described by Simpson et al (1964). 5. Glutathione S-transferase (GST) activity: was measured according to the method of Habig et al (1974).…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…Though this does not directly point to all IAPs, it is known that the aquatic IAP Eichhornia crassipes is able to affect the midgut epithelia tissue of Cx. pipiens [79]. In addition, the fact that leaf litter of certain IAPs enhances the abundance of Culex spp.…”
Section: Potential Effects Of Invasive Alien Plants On Viral Pathogen Transmissionmentioning
confidence: 99%